ANALISA STABILITAS LERENG MENGGUNAKAN PERKUATAN SOIL NAILING PADA SISI KANAN PELIMPAH BENDUNGAN ROTIKLOT KABUPATEN BELU PROVINSI NUSA TENGGARA TIMUR (Eternitas: Jurnal Teknik Sipil, 2025)
This study aims to analyze the slope stability of the right side spillway of Rotiklot Dam in Belu Regency, East Nusa Tenggara, which is dominated by high-plasticity Bobonaro clay with low shear strength. Evaluations were carried out for the existing conditions and after reinforcement using the soil nailing method and its combination with gabions. The analysis utilized Rocscience Slide software and manual calculations. Results indicate that soil nailing increased the slope safety factor from 0.998 to 2.065 under normal conditions, and from 0.708 to 1.436 under seismic conditions. The combination of soil nailing and gabions yielded better results. These findings indicate the effectiveness of slope reinforcement methods as a geotechnical solution in landslide-prone areas.
Keywords: Slope Stability; Soil Nailing; Gabions; Rotiklot Dam; Safety Factor